PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING - Putra, Ade Rama (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research backed by low student learning outcomes in fourth grade at SDN 07 Kecamatan Sungai Aur Kabupaten Pasaman Barat, so outcomes standart in science learning not get it yet. Purpose of the research are described an increased outcomes student in science learning with used Contextual Teaching and Learning  approach. Subject in the research is teacher and student in fourth grade at SDN 07 Kecamatan Sungai Aur Kabupaten Pasaman Barat. The result showed planning, implementation and outcomes student increased.Thus,it is said Contextual Teaching and Learning approach can improve outcomes student in science learning fourth grade of SDN 07 Kecamatan Sungai Aur Kabupaten Pasaman Barat.